COMPARATIVE ANALYSIS OF POLITICAL AND LEGAL MECHANISMS FOR IMPROVING PUBLIC RELATIONS SERVICES IN PUBLIC ADMINISTRATION - Mansur Yunusov (International Journal of Literature and Language Studies, 2026)
This article provides a comparative analysis of political and legal mechanisms for improving public relations services in public administration. It examines the legal regulation of government communication and the influence of political factors on the development of PR activities. Special attention is given to comparing international experience with national models of PR organization. The study analyzes issues of improving information policy efficiency, ensuring transparency and accountability, and strengthening interaction between the state and society.